A Framework to Identify Best Quality Management Practices and Techniques for Diverse Production Ramp-Up Environments: Propositions for Future Research. Issue 1 (1st January 2016) - Leffakis, Zachary Moran
Abstract : Dynamic competitive mechanisms have driven international manufacturers to increase the rate at which new products are introduced to the global market. Introducing new products faster enables firms to sell at higher volumes and prices, resulting in higher profitability. Thus, there is great financial incentive for manufacturers to increase their production ramp-up speed. This analysis focuses on developing a framework to categorize four different types of production ramp-up environments across various manufacturing settings. The framework provides the foundation to identify the best quality management practices and approaches for improving production ramp-up performance based on the degree of product scope and process technology orientation used in the manufacturing system. Furthermore, propositions are developed to guide future empirical research.